2012
DOI: 10.1038/jp.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics supplementation increases intestinal blood flow velocity in extremely low birth weight preterm infants

Abstract: Probiotics administration significantly increases postprandial intestinal blood flow in extremely low birth weight preterm neonates when compared with the placebo group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Butyrate plays an important role in the regulation of transepithelial fluid transport, maintaining epithelial integrity, ameliorating mucosal oxidative status, and inflammation and modulating gut motility and visceral sensitivity (77,78). Evidence from a small, randomized, double-blind, placebo-controlled trial indicated that probiotic supplementation significantly improved the postprandial superior mesenteric artery flow (P = 0.035) (57), which is another possible pathway by which probiotics may improve feed tolerance because a rise in the postprandial mesenteric flow is essential for food digestion (57).…”
Section: Discussionmentioning
confidence: 93%
“…Butyrate plays an important role in the regulation of transepithelial fluid transport, maintaining epithelial integrity, ameliorating mucosal oxidative status, and inflammation and modulating gut motility and visceral sensitivity (77,78). Evidence from a small, randomized, double-blind, placebo-controlled trial indicated that probiotic supplementation significantly improved the postprandial superior mesenteric artery flow (P = 0.035) (57), which is another possible pathway by which probiotics may improve feed tolerance because a rise in the postprandial mesenteric flow is essential for food digestion (57).…”
Section: Discussionmentioning
confidence: 93%
“…As shown in Figure 1, 35 studies met the inclusion criteria [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. Fourteen additional papers were identified from the reference lists of included studies or by “snowballing” techniques [52,56,57,58,59,60,61,62,63,64,65,66,67,68].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies were excluded after examining the full-texts [28,29,31,32,33,35,42,43,44,45,46,47,51,53,54,55,57,58,59,62,63,65,69]. Twenty-five studies were then suitable for inclusion in the systematic review (Table 1) [21,22,23,24,25,26,27,30,34,36,37,38,39,40,41,48,49,50,56,60,61,64,66,68,70].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found the probiotic group reached full feeds sooner and had an increased rate of feeding advancement [9,21]. In contrast, other studies found no difference in the time it took to reach full enteral feedings, the feeding ratio or feeding volume [26,29]. An additional study found no difference in average feeding volume in infants <1000 g but did encounter an increase when stratified to infants with a birthweight between 751-1000 g [8].…”
Section: Effect Of Probiotic Supplements On Enteral Feeding and Gi Tomentioning
confidence: 99%